2023
DOI: 10.1007/s11701-023-01646-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of totally robotic right hemicolectomy: lessons learned from a prospective cohort

Abstract: Robotics facilitates the realization of intra-corporeal anastomosis during right hemicolectomy and allows extracting the operative specimen through a C-section, offering potential benefits in terms of post-operative recovery and incidence of incisional hernia. Therefore, we progressively implemented robotic right hemicolectomy (robRHC) in our centre, and would like to report our initial experience with the technique. Consecutive patients who underwent robRHC within a single centre were prospectively included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…A propensity score-matched analysis of 192 patients who underwent either totally robotic right hemicolectomy (including intra-corporeal anastomosis) or robotic-assisted right hemicolectomy (including extra-corporeal anastomosis) showed that improved post-operative outcomes were reported when using the totally robotic approach, in terms of post-operative pain and recovery of bowel function [ 47 ]. In a prospective cohort study of totally robotic right hemicolectomy [ 48 ], we showed that intra-corporeal anastomosis was achievable in all patients, with a low conversion rate of 3.3% and a reasonable mean operative time of 200.4 ± 114.9 min (which has to be compared to operative times up to 279 min [ 33 ] and 327.5 min [ 49 ] documented in the literature). Moreover, we reported a mean number of harvested lymph nodes of 22.4 ± 7.6, a mean length of stay was of 5.4 ± 3.8 days, a post-operative morbidity of 11.7% and no mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A propensity score-matched analysis of 192 patients who underwent either totally robotic right hemicolectomy (including intra-corporeal anastomosis) or robotic-assisted right hemicolectomy (including extra-corporeal anastomosis) showed that improved post-operative outcomes were reported when using the totally robotic approach, in terms of post-operative pain and recovery of bowel function [ 47 ]. In a prospective cohort study of totally robotic right hemicolectomy [ 48 ], we showed that intra-corporeal anastomosis was achievable in all patients, with a low conversion rate of 3.3% and a reasonable mean operative time of 200.4 ± 114.9 min (which has to be compared to operative times up to 279 min [ 33 ] and 327.5 min [ 49 ] documented in the literature). Moreover, we reported a mean number of harvested lymph nodes of 22.4 ± 7.6, a mean length of stay was of 5.4 ± 3.8 days, a post-operative morbidity of 11.7% and no mortality.…”
Section: Discussionmentioning
confidence: 99%